The psychological function in a Risk Prevention and Protection Service: the assessment of work-related stress risk/psychosocial risk as occasion to promote client orientation. - Atzori, Elisabetta (Rivista di Psicologia Clinica, 2013)
The paper aims to discuss the promotion of psychological function in a Risk Prevention and Protection Service (SPPR) in hospital. From the regulatory aspects regarding safety at work, a reflection is proposed on the difference between the constructs of risk work-related stress risk and psychosocial risk. An intervention of psychosocial risk assessment in SPPR is reported as occasion to study the cultural components of the hospital organization and to promote client orientation about the relationship between workers and patients and between workers and service.